Investigating the effectiveness of emotional design principle to attenuate ego depletion effect. (December 2021) - Le, Yiyang; Chen, Zhongting; Liu, Shuo; Pang, Weiguo; Deng, Ciping
Abstract: An important function of positive emotional design is protecting learning from negative impacts by promoting self-regulation. The present study examines the effects of the emotional design principle in the situation of ego depletion, which reflects a period of self-regulation failure due to a lack of mental resources. Based on a sample of 120 students from a Chinese university, two groups of participants divided into depletion and non-depletion conditions first received different self-regulation manipulations, and then attended a multimedia lesson, with either a positive emotional design or a neutral emotional design. It was found that learning with positive emotional design materials alleviated the decrease in the transfer performance of the depletion group by preventing cognitive overload. These results are consistent with the proposition that implementing an emotional design approach can prevent the impairment of learning. The results also provide preliminary evidence for the assumption that learners' affective states may impact the consumption of their mental resources, and, in turn, affect cognitive load. Additional implications for the role of learners' affective states in cognitive load are discussed. Highlights: The effect of emotional design is examined with psychophysiology measures. The ego depletion effect negatively affects learning performance. Emotional design alleviates the impairment of the ego depletion effect on learning. Emotional design helps the learner reduce his/her cognitive load. Emotional design helps the learner maintain his/her self-regulation strength.